2014
DOI: 10.1097/aln.0000000000000424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reversal of Neuromuscular Blockade with Sugammadex versus Usual Care on Bleeding Risk in a Randomized Study of Surgical Patients

Abstract: Sugammadex produced limited, transient (<1 h) increases in activated partial thromboplastin time and prothrombin time but was not associated with increased risk of bleeding versus usual care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 15 publications
2
41
0
Order By: Relevance
“…Staals et al in a study of patients with renal failure, found sugammadex had no significant effect on AST, ALT, gamma glutamyl transferase levels and PLT counts compared to the control group [28]. In 2014 Rahe-Meyer et al, in a study of patients undergoing joint surgery on the hip or knee, compared the aPTT and PT levels of patients given sugammadex, neostigmine with glycopyrrolate, or atropine or placebo/spontaneous recovery and found limited levels of increase and reported that there was no other increase in incidence of bleeding [21]. Schaller and Fink in an evidence-based compilation reported that if there is a situation that causes risk of bleeding or that may be revealed by not taking extra precautions with sugammadex, the anticoagulant effects of sugammadex may become clear clinically in such situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staals et al in a study of patients with renal failure, found sugammadex had no significant effect on AST, ALT, gamma glutamyl transferase levels and PLT counts compared to the control group [28]. In 2014 Rahe-Meyer et al, in a study of patients undergoing joint surgery on the hip or knee, compared the aPTT and PT levels of patients given sugammadex, neostigmine with glycopyrrolate, or atropine or placebo/spontaneous recovery and found limited levels of increase and reported that there was no other increase in incidence of bleeding [21]. Schaller and Fink in an evidence-based compilation reported that if there is a situation that causes risk of bleeding or that may be revealed by not taking extra precautions with sugammadex, the anticoagulant effects of sugammadex may become clear clinically in such situations.…”
Section: Discussionmentioning
confidence: 99%
“…Again in terms of PT, aPTT, fibrinogen, and D-dimer levels, there was no significant difference between the groups (Tables 2 and 3). Some publications have reported that, though low, there is a potential risk of hemorrhage in the postoperative period due to the minor and temporary lengthening effect of sugammadex administered at the end of the surgical procedure [21,22]. From the point of view of sugammadex and hemorrhagic complications, the European Medicines Agency researched two possible hemorrhagic complications and determined that "obtained proof shows there is an effect of sugammadex on bleeding parameters such as aPTT and PT" [23].…”
Section: Discussionmentioning
confidence: 99%
“…Their findings do not support that 2 or 4 mgkg -1 sugammadex is associated with a longer clotting time. Another double-blinded randomized study enrolling patients undergoing orthopedic surgery confirms that sugammadex does not increase the bleeding risk [87].…”
Section: Longer Clotting Time and Increased Bleedingmentioning
confidence: 95%
“…While sugammadex produced limited, transient (<1 hour) increases in activated partial thromboplastin time and prothrombin time, it was not associated with increased risk of bleeding compared to traditional care modalities [14].…”
Section: Sugammadex and Surgical Bleedingmentioning
confidence: 99%